Psychoanalytic Study of Carl Gustav Jung: Persona in the Character Tang Xin in the Drama “Nǐ Hǎo, Shénqiāngshǒu” Episodes 1-15 by Lian Mu Chu Guang - Mingyue Li; Josephine Kezia Krisyani; Danton Nabilla Putri Herianto; Niswatun Solihatul Azkiyah (Universitas Negeri Surabaya, 2023)
Abstract: Persona is a special intellectual property of Jung. According to him, Persona is a social and psychological construction with a specific purpose. Persona is a mask that can be worn by anyone. Carl Jung chose this mask to see how a person plays a role in representing social and cultural stereotypes, instead of accepting oneself. Persona is a mask that someone shows to display another side of themselves so that they can be accepted by society. Nowadays, it is often found in society that individuals show another side of themselves. There are reasons behind all of that, why someone uses their mask. Sometimes, someone uses it for good reasons, but there are also those who use their mask for less desirable reasons. This research uses a descriptive qualitative method, in which the understanding of Persona based on Carl Gustav Jung's theory in explaining another side of a person is described and presented. It also uses the method of reading and watching the drama 'Hello, The Sharpshooter'.